Chemical Characterization and Antidiabetic Activity of Essential Oils from Pelargonium graveolens Leaves - Javed Ahamad; Subasini Uthirapathy (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2021)
Pelargonium graveolens (Geranium) is a source of the finest quality of fragrance and its essential oils are used as antibacterial, and antifungal agents. The aim of the current research is to determine chemical constituents in the essential oil of P. graveolens by GC-MS and evaluate its antidiabetic activity via α-glucosidase inhibition assay. The chemical composition of P. graveolens essential oil was determined by GC/MS and its antidiabetic activity was assessed through inhibition of α-glucosidase enzyme in in-vitro models. GC-MS analysis determines 36 chemical components in the essential oil of P. graveolens leaves, and citronellyl isovalerate (10.41 %), menthol (9.61 %), linalool (8.63 %), p-menthone (6.31 %), and geranyl tiglate (4.99 %) were recorded as major constituents. The essential oil of P. graveolens leaves showed concentration dependant inhibition of α-glucosidase enzyme ranging from 28.13±1.41 to 74.24±2.53 µg/mL for concentration ranging from 31.25 to 1000 µg/mL. The IC50 values for of P. graveolens and acarbose were found as 93.72±4.76 and 80.4±2.17 µg/mL, respectively against the α-glucosidase enzyme. The study finding explores the chemical components of P. graveolens growing in the Iraqi Kurdistan region and scientifically supported its possible use in diabetic patients for controlling postprandial hyperglycemia.